Determinación de los factores que inciden en la disolución y liquidación de las compañías por sector económico de la provincia de Zamora Chinchipe período 2015-2020 - Celi Zhiñin, Mary Carmen (2022)
The following research work entitled "DETERMINATION OF THE FACTORS INVOLVING THE DISSOLUTION AND LIQUIDATION OF COMPANIES BY ECONOMIC SECTOR IN THE PROVINCE OF ZAMORA CHINCHIPE DURING 2015-2020", was developed in order to discover the factors affecting the dissolution and liquidation of companies by economic sector in the province of Zamora Chinchipe during 2015- 2020. In the province of Zamora Chinchipe, information regarding companies that have gone through dissolution or liquidation by economic sector has been reviewed through the period 2015-2020; this information is available on the Superintendence of Companies, Securities, and Insurance's official website; the codes of the companies were verified based on their corporate names by using the National Classification of Economic Activities guide.. Through a process of gathering information on the companies that entered into dissolution and liquidation, the companies were classified according to the database of the regulatory entity, and thus compile information according to the legal situation, considering the last balance sheet presented. Detailed financial statements including catalogs of each period were downloaded and consolidated with the list of companies in Zamora Chinchipe province to prepare the database. In order to establish the economic-financial situation of the companies, tables and graphs were elaborated based on the reasons for dissolution and liquidation. In compliance with the specific objectives, it was concluded that the application of the financial indicators in the companies in the process of dissolution and liquidation was favorable because it was determined that the companies did not have the necessary liquidity to meet their short-term obligations, with a high level of indebtedness, low sales turnover and minimum profitability. For this reason, it is recommended that the companies apply the financial indicators to the financial statements and make the right decisions.